“Auditoría integral y su incidencia en la gestión administrativa y financiera de la c.t.i.c, cantón Caluma, período 2018”. - Mariuxi Jasmin, Sánchez Cisneros (2020)
The comprehensive audit and its impact on the administrative and financial management of the CTIC, Canton Caluma, period 2018, was carried out with the purpose of evaluating the administrative and financial management and verifying compliance with the laws, regulations and rules applicable to the entity, Investigation techniques have been used, such as observation, which has served to obtain preliminary information. The interview was applied to the manager. After that, internal control questionnaires were used using the COSO I method, applied to the personnel. The identified findings are that the entity does not have a code of ethics to regulate the discipline of the partners, it does not have a process to evaluate and mitigate risks, collections are not deposited daily, there are incompatibilities in the functions of workers, there is no reliability and security in information management. In the financial area, a vertical financial study was carried out, financial indicators were applied. In the performance audit, evaluation questionnaires were used in the direction, management and accounting area to verify compliance with the processes. In the compliance audit it was determined that the entity performed 91% of what is established in the laws and regulations, it is recommended to the cooperative's administrators to take into account the report of the comprehensive audit carried out with the aim of promoting the improvement of both administrative and financial activities.